Analysis of the Effects of Inflation and Unemployment on the Poor Population of North Sumatra in 2001-2020 - Noel Ramot Denvico Tamba; Cut Mutia Saprina Dewi; Inda Serfina Tarigan (Indonesian Journal of Advanced Research, 2023)
The purpose of this research is to identify and analyze the effects of inflation and unemployment on the poor in North Sumatra from 2001-2020. The data used in this study is secondary data obtained from the Central Bureau of Statistics for 2001-2020. The analysis used is regression analysis with the Error Correction Model (ECM) method. The results of this study are (1) Inflation in the short term has a positive and insignificant effect and in the long term Inflation has a positive and significant effect on the poor population in North Sumatra, (2) Unemployment in the short term and long term has a positive and insignificant effect on the population Poor in North Sumatra, (3) The independent variables in the long run in this model, namely Inflation and Unemployment, have a joint and significant effect on the poor population in North Sumatra.